Efficacy of P2Y12 receptor inhibitors in myocardial infarction in individuals carrying different CYP2C19 genotypes living in the northern region of Russia - A. S. Vorobyov; G. I. Lifshits; E. M. Zelenskaya; K. Yu. Batueva; L. V. Kovalenko; I. A. Urvantseva; M. Yu. Donnikov; M. S. Poptsova; E. P. Zbirovskaya; K. Yu. Nikolaev (Российский кардиологический журнал, 2024)
Aim. To evaluate the efficacy of P2Y12 receptor inhibitors (clopidogrel and ticagrelor) in patients with myocardial infarction (MI) living in the northern region of Russia (Khanty-Mansi Autonomous Okrug — Yugra), depending on the carriage of various CYP2C19 allelic variants.Material and methods. This prospective observational study included 218 patients with acute MI who underwent percutaneous coronary intervention (PCI). The patients also underwent determination of allelic variants of the CYP2C19 gene. Patient were divided into groups receiving clopidogrel (n=164, 75%) and ticagrelor (n=54, 25%). Using biostatistical analysis methods, a comparison of clinical and genetic characteristics was performed, as well as an assessment of the risk of ischemic events between the groups in the long-term (108 months, 9 years) post-infarction period.Results. Reduced (*1/*2, *2/*2, *1/*3) and increased (*1/*17, *17/*17) metabolizer CYP2C19 genotypes, as well as severe comorbidity, are reliable independent predictors of composite outcome (cardiovascular death, recurrent acute coronary syndrome, coronary stent/bypass thrombosis, myocardial revascularization, acute ischemic cerebrovascular accident) during a long-term (9 years) follow-up. The advantages of ticagrelor over clopidogrel in terms of the effect on the incidence of ischemic events in the long-term period were established without a significant difference for bleeding both in the general cohort of patients and among carriers of CYP2C19 allelic variants (*1/*2, *2/*2, *1/*3) and (*1/*17,*17/*17) in patients with MI.Conclusion. Ticagrelor is significantly more effective than clopidogrel in reducing the risk of ischemic events in the general cohort of patients, as well as in carriers of reduced (*1/*2, *2/*2, *1/*3) and increased (*1/*17, *17/*17) metabolizer CYP2C19 genotypes during 9-year follow-up after the index MI.